Predicting Conversion to Open Cholecystectomy: A Validation Study of the Difficult Laparoscopic Cholecystectomy Scoring System - Muhammad Hafidh Komar; Imanuddin, Kiagus Ahmad; Theodorus (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Laparoscopic cholecystectomy (LC) has become the gold standard for managing symptomatic gallstone disease. However, a subset of patients requires conversion to open cholecystectomy (OC) due to intraoperative difficulties. The difficult laparoscopic cholecystectomy scoring system (DLCSS) has been proposed to predict the likelihood of conversion. This study aimed to validate the DLCSS in a single-center setting and assess its predictive accuracy for conversion to OC. Methods: A retrospective analysis was conducted on patients who underwent LC at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia, between January and December 2023. Preoperative, intraoperative, and postoperative data were collected. The DLCSS was calculated for each patient, and its correlation with conversion to OC was analyzed using statistical methods. Results: A total of 30 patients were included in the study. The conversion rate to OC was 3.3%. Statistical analysis revealed a weak negative correlation between the DLCSS and conversion to OC (r = -0.318, p = 0.087), suggesting that higher DLCSS scores were associated with a slightly increased likelihood of conversion, although this association was not statistically significant. Conclusion: The DLCSS demonstrated limited predictive value for conversion to OC in our single-center study. Further research with larger sample sizes and diverse patient populations is needed to confirm the utility of the DLCSS in predicting conversion and to identify additional factors that may contribute to intraoperative difficulties during LC.